ANALISIS PENGENDALIAN PERSEDIAAN BAHAN BAKU MENGGUNAKAN METODE ECONOMIC ORDER QUANTITY (EOQ) DI PABRIK XYZ - Yasin Ageng Prasetya; Ayudyah Eka Apsari (KAMPUS AKADEMIK PUBLISING, 2026)
The Factory XYZ is a Micro, Small and Medium Enterprise (MSME) that produces round tofu crackers. MSMEs do not yet have a structured inventory management method for procuring raw materials. The problem that arises is that in January and February there is an excess of raw materials, but in March there is a shortage. Therefore, the purpose of this study is to propose raw material inventory control measures that can be used to avoid shortages or surpluses at minimal cost. This study uses the Economic Order Quantity (EOQ) method. Based on data processing using the EOQ method, the optimal order quantity is 13,516 kg with an order frequency of 16 times per year, a safety stock of 1,515.756 kg, a reorder point of 2,233.096 kg, and total inventory costs of Rp 1,019,072. Therefore, a proposal for controlling the raw material inventory of soybeans at Factory XYZ was obtained by applying the EOQ method, as it could save Rp 3,328,000 or 86.67% in ordering costs.